2001
DOI: 10.1007/s005350170069
|View full text |Cite
|
Sign up to set email alerts
|

KAI1 , CAR , and Smad4 expression in the progression of colorectal tumor

Abstract: These results suggest that the upregulation of CAR and down-regulation of Smad4 are associated with the progression of colorectal tumors, while the upregulation of these genes and of KAI1 seems to be involved in the early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…Kaplan-Meier analysis of the survival curves showed a significantly worse overall and disease-free survival for patients whose tumors had low SMAD4 levels (log-rank test, P = 0.025 and P = 0.013, respectively), indicating that low SMAD4 tumor protein level is a marker of poor prognosis for patients with Dukes C colorectal cancer. This is in agreement with previous studies linking increased SMAD4 mutation frequency and reduced SMAD4 mRNA levels with tumor progression (12,14).…”
Section: Smad4 and Prognosis In Colorectal Cancersupporting
confidence: 94%
See 1 more Smart Citation
“…Kaplan-Meier analysis of the survival curves showed a significantly worse overall and disease-free survival for patients whose tumors had low SMAD4 levels (log-rank test, P = 0.025 and P = 0.013, respectively), indicating that low SMAD4 tumor protein level is a marker of poor prognosis for patients with Dukes C colorectal cancer. This is in agreement with previous studies linking increased SMAD4 mutation frequency and reduced SMAD4 mRNA levels with tumor progression (12,14).…”
Section: Smad4 and Prognosis In Colorectal Cancersupporting
confidence: 94%
“…In addition, frequent somatic mutations have been found in human colorectal tumors in several studies, further suggesting an important role for this gene in colorectal carcinogenesis (11,12). Moreover, animal studies have shown that SMAD4 inactivation is involved in the malignant transformation of gastrointestinal adenomas (13) and a reduction in SMAD4 mRNA levels has been observed during tumor progression (14).…”
mentioning
confidence: 99%
“…KAI-1 expression is high in human normal prostate and benign prostatic hyperplasia, but decreases in a significant way in cancer cell lines derived from metastatic prostate tumors (1), and prostate carcinomas with a low expression level of KAI-1 have shown more aggressive features than those with high expression levels (4). These same characteristics were also reported for pancreatic carcinoma, bladder carcinoma, breast carcinoma, non-small-cell lung carcinoma, gastric carcinoma, esophageal carcinoma, and oral squamous cell carcinoma (2,4,(21)(22)(23)(24). The physiologic and pathologic functions of KAI-1 are largely unknown (4), and it has been proposed that association with other cell-surface proteins may be of utmost importance in directing its biological activities (2).…”
supporting
confidence: 55%
“…Binding to CAR represents the initial event in cell attachment in vitro, and therefore CAR expression levels long have been thought to be critical in determining the transduction efficiency of Ad5 in vivo. Several studies have reported low expression of CAR in primary carcinoma lines and tumor explants (3,21,30,32,37), highlighting the necessity for CAR-independent targeting strategies. However, the nonspecific sequestration of Ad5 in the liver remains the major obstacle to achieving high-efficiency tumor targeting following systemic delivery.…”
mentioning
confidence: 99%